2019
DOI: 10.1186/s43019-019-0014-2
|View full text |Cite
|
Sign up to set email alerts
|

Anterior tibial displacement on preoperative stress radiography of ACL-injured knee depending on knee flexion angle

Abstract: Purpose: To compare side-to-side difference (SSD) of anterior tibial translation in instrumented stress radiography for each series of anterior cruciate ligament (ACL)-injured subjects according to knee flexion angle. Methods: Forty subjects who were suspected of having significant ACL injury by manual Lachman test and MRI were recruited for this prospective study. These subjects took stress radiographs for both knees with corresponding knee flexion of 10°(series M1) and 30°(series M2) using Telos stress devic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 25 publications
(29 reference statements)
0
8
0
Order By: Relevance
“…They found that 28 of 29 (97%) knees exhibited a positive Lachman test, and the average of differential laxity according to the TelosTM device (Telos Medical, Austin and Associates, Millersville, MD, USA) was 8.3 mm (range, 5 to 13 mm). Anterior instability can be seen in ACL-deficient knees, and >5 mm of anterior tibial translation is generally considered as a cut off value for ACL reconstruction [ 19 , 20 ]. However, two patients underwent subsequent ACL reconstruction.…”
Section: Discussionmentioning
confidence: 99%
“…They found that 28 of 29 (97%) knees exhibited a positive Lachman test, and the average of differential laxity according to the TelosTM device (Telos Medical, Austin and Associates, Millersville, MD, USA) was 8.3 mm (range, 5 to 13 mm). Anterior instability can be seen in ACL-deficient knees, and >5 mm of anterior tibial translation is generally considered as a cut off value for ACL reconstruction [ 19 , 20 ]. However, two patients underwent subsequent ACL reconstruction.…”
Section: Discussionmentioning
confidence: 99%
“…Overall, 20 devices/techniques were used in the assessment of more than one plane of stability throughout the literature. These included the Telos device (Metax, Hungen‐Obbornhofen, Germany) [1–4, 9, 16, 25, 29, 30, 37, 41–45, 47], manual force [4, 13, 14, 32, 39, 46, 52, 53], hydraulic force [20–22], S‐type load cell [12, 27, 28, 31, 32, 38], a constant‐tension spring [31, 32], and the dynamic stress test using active muscle contraction [1, 7, 25]. The stress techniques described in the presented review are summarized in Table 3.…”
Section: Resultsmentioning
confidence: 99%
“…The procedure of applying the stress and the magnitude of the applied stress differed among different presented studies as well as based on the utilized stress technique. The Telos device was the most commonly used stress device in the ACL and PCL studies [1, 2, 4, 8–10, 16, 25, 30, 37, 41–45, 47, 48].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…However, exact matching for meniscal and ligamentous injuries is hardly feasible in a retrospective single-center study design. Other confounding factors to be considered to influence tibial internal rotation are knee flexion [ 45 ] and quadriceps activity [ 46 ]. Both factors, most likely, can be neglected due to uniform positioning of the knees in the MRI coil and absence of active voluntary quadriceps muscle contraction during image acquisition.…”
Section: Discussionmentioning
confidence: 99%